Modelling and simulation of self-excited induction generator driven by a wind turbine - Ghanim, Ammar Shamil; Alsammak, Ahmed Nasser B. (Eastern-European Journal of Enterprise Technologies, 2020)
The excellent specifications of the isolated squirrel cage self-excited induction generator (SEIG) make it the first choice for use with renewable energy sources. However, poor voltage and frequency regulation (under load and speed perturbations) are the main problems with isolated SEIGs. Wide dependence on the SEIG requires prior knowledge of its behaviour with regard to variations in the input of mechanical power and output of electrical power to develop a control system that is capable of maintaining the voltage and frequency at rated values, as far as possible, with any change in the input or output power of the SEIG. In this paper, a mathematical model of a wind energy conversion system (WECS) based on a squirrel cage SEIG with a generalized impedance control (GIC) was built using the Matlab/Simulink environment in a d-q stationary reference frame. A fuzzy logic controller (FLC) was used to control the parameters of the GIC. The training of the FLC was conducted by a neural network through Matlab’s Neuro-Fuzzy designer. The results of this paper showed that the trained FLC succeeded in controlling the real and reactive power flow between the SEIG and the GIC system, in which the maximum variation for both magnitude and frequency of the generated voltage with any load or wind speed perturbation will not exceed (0.2 %) for the frequency and (3 %) for the voltage magnitude in both directions. The SEIG model was validated by comparing the results obtained with those of well-known studies with the same rating and operating conditions